1969
DOI: 10.1029/jb074i025p05867
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of rocks and their significance for lunar radar observations

Abstract: A wide variety of terrestrial rocks has been investigated to determine the range of variation of the high-frequency electrical properties. Both solid rocks and powders of various types have been measured at frequencies of 450 MHz and 35 GHz; some measurements have been made at elevated temperatures. Solid materials show wide variations in permittivity and absorption length, but apart from a small trend with silica content it is not clear that there is any pattern to the variations, and it is unlikely that meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
196
1

Year Published

1984
1984
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 311 publications
(215 citation statements)
references
References 8 publications
(4 reference statements)
18
196
1
Order By: Relevance
“…The bulk porosity of the nucleus is thus quite high, ranging from 70 to 80% . In agreement with the bulk density dependence derived from mixing formulae (Campbell & Ulrichs 1969), measurements on porous granular samples confirmed that, as expected, the dielectric constant value (which is the real part of the relative permittivity) systematically decreases with increasing porosity (Heggy et al 2012;Brouet et al 2014) with a typical slope value of about −4.7 × 10 −2 per percent at 90 MHz (Brouet et al 2015).…”
Section: Permittivity Valuessupporting
confidence: 68%
“…The bulk porosity of the nucleus is thus quite high, ranging from 70 to 80% . In agreement with the bulk density dependence derived from mixing formulae (Campbell & Ulrichs 1969), measurements on porous granular samples confirmed that, as expected, the dielectric constant value (which is the real part of the relative permittivity) systematically decreases with increasing porosity (Heggy et al 2012;Brouet et al 2014) with a typical slope value of about −4.7 × 10 −2 per percent at 90 MHz (Brouet et al 2015).…”
Section: Permittivity Valuessupporting
confidence: 68%
“…Pumice, volcanic ash, and tuff have permittivity values between ∼2.5 and 3.5, while basalts have ε values around 7 to 9 (Campbell and Ulrichs, 1969). Pure water ice has a permittivity of ∼3.1 (Cumming, 1952).…”
Section: Physical Properties Of the Medusae Fossae Formation Materialsmentioning
confidence: 99%
“…The depth of the main contributing layer depends on the material opacity, which is unknown. Measurements for rocks showed that in most materials this depth lies between 3 and 100λ (Campbell & Ulrichs 1969). A depth of 10λ is commonly used when dealing with planetary surfaces (e.g.…”
Section: Emissivity and Depth Effectmentioning
confidence: 99%